2 answers:
14.08 that’s if in this case “of” means multiply hope this helps
Answer:
14.08
Step-by-step explanation:
You might be interested in
Answer:
3x+2y+2=0
3x=-2y-2
x=-(2y+2)/3
Step-by-step explanation:
Answer:
<em>see</em><em> </em><em>explanation</em>
Step-by-step explanation:
f(x)= -2(x²+8x+16)-5
![-2 {x}^{2} - 16x - 32 - 5 \\ f(x)= - 2 {x}^{2} - 16x - 37](https://tex.z-dn.net/?f=%20-2%20%7Bx%7D%5E%7B2%7D%20%20-%2016x%20-%2032%20-%205%20%5C%5C%20%20f%28x%29%3D%20-%202%20%7Bx%7D%5E%7B2%7D%20%20-%2016x%20-%2037)
Answer:
Step-by-step explanation:
![log_{3}(81) = 4 \\ \\ 81 = {3}^{4}](https://tex.z-dn.net/?f=%20log_%7B3%7D%2881%29%20%20%3D%204%20%5C%5C%20%20%5C%5C%2081%20%3D%20%20%7B3%7D%5E%7B4%7D%20)
A has the solution of -2/3.
Hello :
<span> f(x) + g(x) =x²+10 +x-3
</span><span> f(x) + g(x) = x²+x+7</span>